Microsoft Touch Develop and the BBC micro:bit - Ball, Thomas; Protzenko, Jonathan; Bishop, Judith; Moskal, Michal; Halleux, Jonathan "Peli" de; Braun, Michael; Hodges, Steve; Riley, Clare (ICSE 2016 Companion, 2016)
The chance to influence the lives of a million children does not come often. Through a partnership between the BBC and several technology companies, a small instructional computing device called the BBC micro:bit will be given to a million children in the UK in 2016. Moreover, using the micro:bit will be part of the CS curriculum. We describe how Microsoft's Touch Develop programming platform works with the BBC micro:bit. We describe the design and architecture of the micro:bit and the software engineering hurdles that had to be overcome to ensure it was as accessible as possible to children and teachers. The combined hardware/software platform is evaluated and early anecdotal evidence is presented. A video about the micro:bit is available at http://aka.ms/bbcmicrobit.